MINANGKABAU TRADITIONAL ART AS A NATION CHARACTER BUILDING - Iman Laili; Eriza Nelfi (International Conference on Languages and Arts, 2014)
This paper is aimed at revealing the good values in Minangkabau traditional art of  oral tradition. This oral tradition is tale and poetry; it has signature values as the legacy of our ancestors such as: mutual respect, religious, togetherness, compassion, forgive each other, never give up/working hard, always grateful, discipline, and deliberation.   Keywords: Minangkabau traditional art, oral tradition, Minangkabau